To kill or not to kill: A systematic literature review of high-stakes moral decision-making measures and their psychometric properties - Ni, Benjamin Kai; Burns, Bruce D.; Mak, Karina K. L.; Lah, Suncica; Silva, Diego S.; Goldwater, Micah B.; Kleitman, Sabina (Frontiers in Psychology, 2023)
The present systematic review investigates the psychological tools are available for capturing high-stakes decisions involving life-death content and their psychometric properties. Valid measurement of these individual differences will provide crucial information in the personnel selection and training in fields where high-stakes moral issues exist (e.g., military, medicine). To our knowledge, this is the first systematic examination of such instruments. Method: Systematic searches of 6 electronic databases were conducted according to the PRISMA guidelines. An appraisal tool evaluated the quality of identified measures. Twenty studies met pre-determined inclusion criteria. Moral decision-making was assessed with either a self-report scale (n = 3) or moral dilemmas (n = 17). Results: The findings identified two measures, the Defining Issues Test and the Oxford Utilitarian Test as psychometrically sound measures of moral decision-making. However, they are unlikely to be considered “gold standard” measures due to their theoretically specific, but limited, scope. Overall, the findings suggest that research in the area has been scattered. There is a lack of consensus on the definition of moral decision-making, and a lack of cross-validation on how different measures of moral decision-making relate to each other. This presents a gap between theory and empirical measurement in moral decision-making. Further work is needed for a unified conceptualisation of moral decision-making to pave the way to both theory development and the development of well-validated measurement tools, and this review provides a critical foundation for both.